Presenting an experimental model to investigate the effect of changing the dimensions of macro-synthetic-fiber-reinforced concrete on fracture energy - abolfazl hassani (Iranian Society of Structrual Engineering (ISSE), 2020)
Concrete has a brittle behavior as one of the most frequently used construction materials. Adding fibers to concrete can enhance its ductility and some of its mechanical properties. For this purpose, a laboratory study was conducted in order to present an experimental model to investigate the effect of size of micro-synthetic-fiber-reinforced concrete on fracture energy changes. In this study, concrete beam specimens were manufactured and evaluated with three different thicknesses and widths. Results indicated that by increasing the thickness of the specimens, fracture energy was respectively increased by 15.3-63.1%. Moreover, by increasing the width of the specimen, fracture energy was respectively increased by 42.04-50.72 %.Fiber-reinforced concrete is a type of concrete that is mixed with fiber. Various types of fibers are used to produce fiber-reinforced concrete, which include glass, polymer, carbon and steel .In the present research, macro-synthetic polymer fibers were used. Some of the consequences of applying macro-synthetic fibers in concrete include reduced shrinkage of fresh and hardened concrete, increased ductility, vulnerability and hardness of concrete, increased strength against fatigue stresses, increased durability and lifetime of concrete, improved concrete mechanical properties (tensile strength, flexural strength, etc.), control of secondary/thermal cracks of concrete, preventing the in-depth propagation of cracks, post-cracking chargeability and reduced permeability against chloride and sulfate ions . To date, numerous studies have been conducted on fiber-reinforced concrete, most of which have been focused on the evaluation of fiber-reinforced concrete using steel and plastic fibers or their combination.